Effect of Ginger Extracts and Storage Temperature on Shelf Life of Kent Mango Fruits - Adams, Abdul-Rahaman; Salifu, Abdul Wahab; Chonga, John; Thomas , Bayuo (Journal of Postharvest Technology, 2016)
Postharvest loss is a major problem affecting fresh mango trade in most developed and developing nations. The ability of mango farmers, distributors, processors and consumers to use natural plants extracts and solutions to maintain fruits quality will significantly affect quality and return on investments. This research was conducted to discover the effects of immersion tomato fruits in dissolved ginger extracts on Total Soluble Solid, Weight loss, pH, Flesh firmness, Pulp cube texture and Consumer acceptance of Kent mango fruits stored at 5°C and 25°C for 12 days. One hundred and twenty eight (128) Kent mango fruits were used for the experiment. The entire sample was divided into four and each division was replicated two times. The research confirmed that the treatment that reduced weight loss better was shown by Twenty minutes solution for 5°C with 4.5%. Also, immersing of mango fruits in dissolved ginger extract for 30 minutes at 25°C was appropriate in TSS and pH which resulted in better taste. In respect of the flesh firmness a short immersing duration at 5°C was found with the best sweet taste keeping the flesh firmness better. In all the cases immersing of fruits sample in dissolved ginger extract resulted in better quality than non-treated samples. Therefore , based on the results produced it can safely be concluded that immersing of Kent mango fruits in dissolved ginger extract offered a promise for adoption for small scale postharvest management of Kent mango fruits.